2016
DOI: 10.3354/meps11924
|View full text |Cite
|
Sign up to set email alerts
|

Invasive lionfish Pterois volitans reduce the density but not the genetic diversity of a native reef fish

Abstract: The Indo-Pacific red lionfish Pterois volitans has spread throughout the western Atlantic causing declines in biomass and diversity of native species at local reefs; worst-case scenarios predict species extinctions and ecosystem phase shifts. While reductions in reef fish population density and recruitment are evident, it is not known whether lionfish are reducing genetic diversity of native species, a major driver of extinction in natural populations. A before-after control-impact experiment was used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Although the experiment was confounded by possible effects of the Deepwater Horizon oil spill, there was a clear indication that smaller resident fishes were less abundant following the invasion. Working in Panama, Palmer et al (2016, this TS) conducted a shorter-term lionfish removal experiment that also indicated a negative effect on the abundance of several native fishes, yet no effect on the genetic diversity of the bicolor damselfish Stegastes partitus.…”
mentioning
confidence: 99%
“…Although the experiment was confounded by possible effects of the Deepwater Horizon oil spill, there was a clear indication that smaller resident fishes were less abundant following the invasion. Working in Panama, Palmer et al (2016, this TS) conducted a shorter-term lionfish removal experiment that also indicated a negative effect on the abundance of several native fishes, yet no effect on the genetic diversity of the bicolor damselfish Stegastes partitus.…”
mentioning
confidence: 99%
“…Although the Mediterranean lionfish invasion is still at its early stage (first reported established populations in Lebanon and Cyprus in 2015) (Jimenez et al 2016, Azzurro & Bariche 2017), selective predation and prey naiveté may have substantial population impacts on a range of native prey species (Albins & Hixon 2013, Peake et al 2018, Côté & Smith 2018). Such impacts are expected to be in line with biodiversity impacts of the western Atlantic lionfish invasion, which has been linked to significant changes in native fish community, including reductions in prey species density, biomass, recruitment, richness (Albins & Hixon 2008, Benkwitt 2015, Albins 2015, Palmer et al 2016), and even local species extirpation (Ingeman 2016). Ultimately, as the Mediterranean lionfish are at the beginning of the spreading stage of the invasion process (Chapple et al 2012), is still unknown whether the behavioural and life-history traits measured in this study will be adaptive for a pan-Mediterranean invasion, where different thermal-regime and oceanographic conditions occur (Johnston & Purkis 2014).…”
Section: Discussionmentioning
confidence: 97%
“…For example, Morris and Akins (2009) found that the mean size of teleost prey for all lionfish in their study, including lionfish up to 40cm TL, was between 1.5 and 2.5cm TL. Many of the fish families that suffer the greatest reductions (Albins & Hixon, 2008;Albins, 2013;Benkwitt, 2015;Ingeman & Webster, 2015;Benkwitt, 2016;Palmer et al, 2016;Tuttle, 2017) and comprise the largest proportion of lionfish gut contents (Layman & Allgeier, 2012;Valdez-Moreno et al, 2012;Côté, Green & Hixon, 2013;Rocha et al, 2015;Harms-Tuohy, Schizas & Appeldoorn, 2016) either seldom achieve 6cm TL (many apogonids, blenniids, gobiids, etc.) or are far more vulnerable to lionfish predation as 0-5 cm TL juveniles (labrids, pomacentrids, grammatids, etc.…”
Section: Lionfish Have the Strongest Effects On 1-5cm Tl Preymentioning
confidence: 99%
“…In a controlled experiment, Albins (2015) demonstrated that lionfish caused declines in prey density, biomass, and species richness on large, isolated coral reefs ranging in area from 1400 to 4000 m 2 . Palmer et al (2016) report the results of a non-replicated manipulative BACI experiment, also conducted on large, isolated coral reefs (> 1200 m 2 ), which demonstrated a strong, negative effect of lionfish on two-of-three native prey species examined. Other experimental manipulations on medium-to-large coral patch reefs (Benkwitt, 2016: 8 to 33 m 2 , : 100 to 150 m 2 , Ingeman, 2016: 140 to 1400 m 2 , Tuttle, 2017: 12 to 35 m 2 ) and in karst solution holes (Ellis & Faletti, 2016: 1.7 to 7 m 2 ) have demonstrated strong negative effects of lionfish on native fishes.…”
Section: Correcting the Record On Experimental And Observational Evidmentioning
confidence: 99%